The telegraph and modern banking development, 1881–1936 - Lin, Chen; Ma, Chicheng; Sun, Yuchen; Xu, Yuchen (Journal of Financial Economics, 2021)
The telegraph was introduced to China in the late 19th century, a time when China also saw the rise of modern banks. Based on this historical context, this paper documents the importance of information technology in banking development. We construct a data set on the distributions of telegraph stations and banks across 287 prefectures between 1881 and 1936. The results show that the telegraph significantly expanded banks’ branch networks in terms of both number and geographic scope. The effect of the telegraph remains robust when we instrument it using proximity to the early military telegraph trunk.